SOURCES OF MATERIAL FOR THE LINXI GRANITOIDS, THE SOUTHERN SEGMENT OF THE DA HINGGAN MTS.: WHEN AND HOW CONTINENTAL CRUST GREW? - Liu W.; Pan X.F.; Xie L.W.; Li H. (My University, 2007)
Sensitive high-resolution ion microprobe (SHRIMP) U-Pb dating and laser-ablation multi-collector ICPMS Hf isotope analyses are conducted on inherited/antecrystal and magmatic zircons from the Linxi granitoids, in the southern segment of the Da Hinggan Mts. of China. SHRIMP dating establishes an Early Cretaceous (135-125Ma) age for most Linxi granitoids and the age of their source rocks at ∼146Ma. However, some granitoids were intruded in the Early Triassic (241Ma) and the terminal Late Jurassic (146Ma), whilst their respective source rocks were generated at 263Ma and 165Ma. A total of 100 SHRIMP analyses yield 206Pb/238U ages younger than 30Ma, whereas all 175 Hf isotope analyses give high positive εHf(t) values. These results indicate juvenile source materials in the lower crust with a notable absence of Precambrian basement. At a given εNd(t), Linxi granitoids exhibit distinctly higher zircon εHf(t) than both the terrestrial array and the Hawaiian basalt array. This Hf-Nd isotopic decoupling suggests a source component of pelagic sediments, i. e. Paleozoic subduction accretion complexes. Zircon εHf(t) values (t = 263 ∼165 Ma) form a trend sub-parallel to the depleted mantle Hf isotope evolution curve, but those (t = 146 ∼125Ma) markedly fall below the latter. The first trend indicates a provenance from essentially the MORBs. However, the abrupt εHf(t) decrease, together with extensive Early Cretaceous magmatism, is interpreted as reflecting mantle upwelling and resultant underplating, and exhumation of subducted oceanic crust. Quantitative simulation shows that Suite 2 granitoids derive from underplated mafic rock, Paleozoic subduction accretion complex, and subducted MORB slices in descending order of mass fractions. However, the Xiaochengzi intrusion (Suite 1) occurring southwest of Linxi derives mainly from Paleozoic subduction accretion complex with a quantity of underplated mafic rocks. Among each of these 5 intrusions, magmatic zircons exhibit systematically decreased 176Hf/177Hf as compared with that of inherited/antecrystal zircons. Growth stages of zircons with t = 146-125Ma tend to decrease in 176Hf/177Hf from center to margin, or show systematic variations. The above results suggest that expansion of the melting region and widening of compositional range occurred in the lower crust over the period between incipient source rock melting and the terminal melting episode during production of Linxi granitoids. The magnesian or I-type geochemical characteristics of Suite 1 granitoids is attributed to a source reservoir of relatively oxidized and hydrous oceanic crust. However, a heterogeneous source that consists of relatively reduced, anhydrous underplated tholeiites and hydrous Paleozoic subduction-accretion complex causes geochemical signatures of Suite 2 granitoids that exhibit affinity to A-type granites but range from typical to less pronounced ferroan.
Keywords: CONTINENTAL CRUST GROWTH; INHERITED/ANTECRYSTAL ZIRCON FROM JUVENILE SOURCE ROCKS; OCEANIC CRUST; SUBDUCTION ACCRETION COMPLEX; UNDERPLATING; Mesozoic::Cretaceous; Мезозой::Меловая